Plasma cell marker, immunoglobulin J polypeptide, predicts early disease-specific mortality in HPV+ HNSCC. Issue 3 (18th March 2021) - Gui, Shanying; O'Neill, W Quinn; Teknos, Theodoros N; Pan, Quintin
Abstract : Background: Patients with human papillomavirus (HPV+) head and neck squamous cell carcinoma (HNSCC) have superior prognoses compared with patients with HPV− HNSCC and strategies for treatment de-escalation are under investigation for the HPV+ setting. However, the survival advantage associated with HPV is not universal, and a subset of patients with HPV+ HNSCC fail definitive treatment and progress with metastatic/recurrent disease. Currently, no biomarker is available to distinguish aggressive from indolent HPV+ HNSCC. Immune dysfunction facilitates tumorigenesis and is associated with poor treatment response; therefore, we hypothesized that diminished intratumoral immune cell functionality may be attractive biomarkers to identify patients with HPV+ HNSCC at risk for early disease-specific mortality. Methods: This is a retrospective analysis of The Cancer Genome Atlas (TCGA) HPV+ HNSCC cohort. Results: Immunoglobulin J polypeptide (IGJ), uniquely expressed in plasma cells, showed a broad expression range in HPV+ HNSCC. Cox regression model, adjusting for clinical covariates, indicated that IGJ is an independent prognostic biomarker for disease-specific survival (DSS) and overall survival (OS). Patients with low IGJ had a 7.2-fold (p<0.001) increase in risk of disease-specific death with a median DSS of 13 months. Low IGJ showed an area under curve (AUC) of 0.89 with 91.0% sensitivity and 87.6% specificity to identify early disease-specific mortality (defined as DSS ≤12 months). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed a global dampening of immune pathways in low IGJ tumors. Conclusions: Our work showed that IGJ is a robust and independent prognostic biomarker for disease-specific mortality in HPV+ HNSCC. Patient with HPV+ HNSCC with limited adaptive immune functionality should not be candidates for treatment de-escalation modalities.